2014
DOI: 10.17547/kjsr.2014.22.4.231
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Korean Version of Mindfulness Based Stress Reduction Program on Stress and Distraction of University Students

Abstract: The purpose of this research was to investigate the effect of K-MBSR on distraction by stress. Subjects were 13 male and female college student. K-MBSR practiced in 6 students and they were practiced for 8 weeks. The control group were 7 students. All the subjects had pre-test and post-test with PSS, KIMS and ANT. In the results of PSS there was significant interaction effect between time (pre-post) and groups. The meditation group showed a lower level than control group in post. In the results of KIMS there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…These studies have found mindfulness-based practices effective for people to reduce stress. In Korea, research on the effects of mindfulness practices on psychological and physical aspects has been rapidly increasing among adults, including university students [18][19][20]. However, studies of mindfulness practice's influence on brain waves (central nervous system; CNS) and the autonomic nervous system (ANS) among Korean university students are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found mindfulness-based practices effective for people to reduce stress. In Korea, research on the effects of mindfulness practices on psychological and physical aspects has been rapidly increasing among adults, including university students [18][19][20]. However, studies of mindfulness practice's influence on brain waves (central nervous system; CNS) and the autonomic nervous system (ANS) among Korean university students are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, thanks to Kabat Zinn's MBSR, mindfulness meditation has proved its efficacy in medicine beyond religious boundaries. Moreover, in South Korea, MBSR has been introduced, modified, and applied to various fields (e.g., medicine, education) by constituting a "Korean Version of Mindfulness-Based Stress Reduction" (K-MBSR) (Bae and Chang 2006;Yoon 2014). Mindfulness, which was passed from Asia to the West, is returning from the West to the East again.…”
Section: Mindfulness Of Death In Early Buddhist Textsmentioning
confidence: 99%
“…The effectiveness of mindfulness in reducing stress has been validated through various research studies ( Yoon, 2014 ; Gotink et al, 2015 ). Based on previous research, we can expect that mindfulness will also have an impact on stress reduction among the elderly population ( Jeun and Son, 2012 ; Lee et al, 2021 ; Kim and Kim, 2023 ).…”
Section: Introductionmentioning
confidence: 99%